Identification of microtubule-associated biomarkers in diffuse large B-cell lymphoma and prognosis prediction - Wu, Wenqi; Liu, Su; Tian, Linyan; Li, Cheng; Jiang, Yanan; Wang, Jinhuan; Lv, Yangyang; Guo, Jing; Xing, Donghui; Zhai, Yixin; Sun, Huimeng; Li, Yuhang; et al. (Frontiers in Genetics, 2023)
Background: Diffuse large B-cell lymphoma (DLBCL) is a genetically heterogeneous disease with a different prognosis. Even though various prognostic evaluations have been applied currently, the prognosis assessment and effective treatment strategy need further exploration. The development of microtubule-associated genes (MAGs) is promising for predicting prognosis in DLBCL. In the present study, we constructed a novel prognostic model based on MAGs. Methods: A total of 33 normal controls and 1360 DLBCL samples from the Gene Expression Omnibus (GEO) database were included. Subsequently, the least absolute shrinkage and selection operator (Lasso) penalized Cox regression, univariate and multivariate Cox regression analysis was performed using R.4.1.1 software. Results: A risk score model based on fourteen candidate MAGs (CCDC78, CD300LG, CTAG2, DYNLL2, MAPKAPK2, MREG, NME8, PGK2, RALBP1, SIGLEC1, SLC1A1, SLC39A12, TMEM63A, and WRAP73) was established. We built a nomogram concerning MAGs and clinical features. Time-dependent receiver operating characteristic (ROC) curves and calibration curves showed reliable prognostic prediction. Kaplan-Meier (K-M) curves suggested that the low-risk group appeared to have better clinical survival outcomes in different subgroups. Furthermore, we made drug sensitivity detection and predicted the response to chemotherapy in different risk score groups. A knocking-out experiment of TMEM63A was conducted and yielded good validity. Conclusion: A novel MAGs prognostic predictive model was built and showed well-performed reliability. Furthermore, candidate genes have potential therapeutic target in DLBCL. More explorations are warranted in DLBCL in the future.